Será a Nigéria um Estado falhado? O grupo Boko Haram - Cierco, Teresa (2016)
The current situation in Nigeria motivates a reflection on the State and the functions it plays in society. The rise of Islamic fundamentalism in the country arises in a complex context of structural problems that puts in question the authority and legitimacy of the State. The clear weakness of institutions and the fragile response by the State to instability and insecurity caused by extremist groups such as Boko Haram, leads us to question whether Nigeria can be considered a failed State. And in the case of a failed State where internal security is in deficit and interethnic conflicts proliferate, will national unity be compromised or seriously threatened? In this article we try to assess the extent to which Islamic fundamentalism has affected the human and economic development in Nigeria and examine how the government has tried to solve the problem.